(untitled) (Journal of the College of Basic Education, 2023)
Modern critical studies tend to make the literary text a linguistic text first.The linguistics of the text is a must because the facts of style ((can only be captured at the level ofLanguage)), (1) The study of style went through two important phases, the first of which was studied within the science ofRhetoric was at the level of Arabic or European studies, as it was determined throughThe data of the science of rhetoric is nothing else.The second stage in the study of style is the one in which style is liberated from rhetoric.Gradually, later on, it became an independent science with its own principles, sayings, and procedures.Descriptive instead of normative science of rhetoric (2) As the style passed through two implicit and independent phases.He did not settle for a single comprehensive definition that would prevent him, and he looked at it from multiple and different angles.Many definitions since Buffon said ((Style is the man himself)), (3) untilModern linguistic and linguistic studies, which said, according to Todorov, that ((style isThe two men)) after discovering the recipient’s role in the style process. (4)These points of view varied in looking at the style, and the researchers limited them toThree: The first: focuses on the originator or creator of the literary text.The second: on the recipient. And the third: on the literary text itself, based on its author, which focuses onthe originator and seek the keys to style in his personality, because his style reveals his thinking style, whichFocuses on the recipient, solicits ((the style keys in the reactions and responses that he gives